Penerapan Metode VAR-X untuk Pemodelan Data Deret Waktu dengan Calendar effects - Ade Gusalinda; I Made Sumertajaya; Septian Rahardiantoro (Xplore: Journal of Statistics, 2019)
One of the commodities that has quite varied price fluctuations is broiler and carcass chicken. The context of forecasting is quite important considering the policies that can be taken by the producer and even the strategies that can be taken by consumers. This study attempts to modeling broiler and carcass prices together with Vector Autoregressive (VAR) which is one method in time series analysis that utilizes more than one time series variable. In addition, the effect of calendar calendar events is also the topic of discussion in this study which is implemented by the VAR-X method. As a result, the calendar effects variables that affect broiler and carcass prices are February, the first week of Ramadan and Eid-ul-Fitr. Furthermore, forecasting with VAR-X produces a pretty good value than VAR with lower MAPE criteria.